EFEKTIVITAS KEBIJAKAN PENJARINGAN ASPIRASI MASYARAKAT MELALUI RESES DPRD PROVINSI JAWA TIMUR DAERAH PEMILIHAN I KOTA SURABAYA - Mario Malem Samosir; Tukiman (Journal Publicuho, 2024)
This study aims to analyze and determine the Effectiveness of The Policy of Community Aspiration Finishing Through the Recess of The DPRD Of East Java Province, Electoral Region I, Surabaya City. This study uses a descriptive qualitative approach to evaluate the effectiveness of the reses policy implemented by the East Java Provincial People's Representative Council (DPRD) in Electoral District 1 of Surabaya. The research focuses on public participation, challenges faced, and the impact of reses on public policy. Data were collected through interviews, observations, and document analysis, which were then analyzed using thematic analysis techniques. The success of the reses program is measured by how well the community’s aspirations are received and translated into relevant public policies. The main challenge identified is the low public participation, attributed to insufficient socialization and a lack of trust in the follow-up process of aspirations. Improvements in socialization, the use of technology, and transparency in follow-up can enhance the effectiveness of reses and the policies generated. The study found that the reses program in Electoral District 1 of Surabaya is effective in capturing public aspirations, with high participation rates, quick responses, and tangible policy impacts. However, resource limitations and the absence of formal surveys reduce its effectiveness. Nevertheless, direct interactions show that the program has succeeded in bridging communication between the legislative body and the public.